Contraceptive Use and Consistency in U.S. Teenagers’ Most Recent Sexual Relationships - Manlove, Jennifer (2004)
CONTEXT: Most U.S. teenage pregnancies are unintended, partly because of inconsistent or no use of contraceptives. Understanding the factors associated with contraceptive use in teenagers’ most recent relationships can help identify strategies to prevent unintended pregnancy. METHODS: Data on 1,468 participants in Waves 1 and 2 of the National Longitudinal Study of Adolescent Health who had had two or more sexual relationships were analyzed to assess factors associated with contraceptive use patterns in teenagers’ most recent sexual relationship. Odds ratios were generated through logistic regression. RESULTS: Many relationship and partner characteristics were significant for females but nonsignificant for males. For example, females’ odds of ever, rather than never, having used contraception in their most recent relationship increased with the duration of the relationship (odds ratio, 1.1); their odds were reduced if they had not known their partner before dating him (0.2). The odds of consistent use (vs. inconsistent or no use) were higher for females in a “liked” relationship than for those in a romantic relationship (2.6), and for females using a hormonal method instead of condoms (4.5). Females’ odds of consistent use decreased if the relationship involved physical violence (0.5). Among teenagers in romantic or “liked” relationships, the odds of ever-use and of consistent use were elevated among females who had discussed contraception with the partner before their first sex together (2.9 and 2.1, respectively), and the odds increased among males as the number of presexual couple-like activities increased (1.2 for each). CONCLUSIONS: Teenagers must use contraception consistently over time and across relationships despite pressure not to. Therefore, they must learn to negotiate sexual and contraceptive decisions in each relationship.